Economic integration and manufacturing concentration patterns: Evidence from Mercosur - Iulia Traistaru; Christian Volpe Martincus (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2003)
Trade policy changes are likely to result in a reallocation of resources across sectors and space. Over the past two decades, Argentina, Brazil, Paraguay, and Uruguay have implemented unilateral trade liberalization programs and formed a regional bloc, Mercosur. The effects of these reforms on production structures in these countries have not received a great deal of attention. Have patterns of manufacturing concentration changed? What are their main determinants? This paper analyses relative manufacturing concentration patterns in Argentina, Brazil, and Uruguay over the period 1985-1998. The econometric evidence indicates that localization of demand and comparative advantages are the main driving forces of these patterns. The establishment of Mercosur seems to have played a role in the spatial distribution of manufacturing in the above three countries.
Keywords: L60; F14; F15; C23; 330; Economic Integration; Concentration of Industries; Comparative advantage; Economic Geography; Mercosur